Tecnociencia, vigilancia y sistema penal: la superación de paradigmas y las nuevas perspectivas bajo el punto de vista tecnológico - Hauck, Joao R. (2009)
This text approaches the advance of technoscience and the social pathologies which happen as a result of its use. The objective is to demonstrate that the actual scientific reality, which guides the phenomenon of contemporary world, is not at the pace of the archaic system of penal justice. At the end, some comments are made about the electronic monitoring of offenders, once such\ntechnology has been considered as a useful tool to promote the "fall of the walls" which separate convicts and society